Information System Employee Attendance at PT. Sigma Cipta Caraka Web-Based Using Coloring and Sequential Search Methods - Avi Khoirun Nizam; F Fauziah; Albaar Rubasy (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
At PT. Sigma employee attendance is still done manually by hand writing into a book by entering the hours of arrival and hours of leaving work. From the TDS unit, the process that was carried out manually was found to be a problem where attendance was not appropriate. Difficult to trace, and a high risk of data loss. On the other hand, employees who work with assignments to leave the office have not been accommodated so employees who are outside the office must return to the office to fill in attendance manually by writing a hand, so a computerized attendance system is needed and can be accessed by employees who are on duty outside the office. by connecting to the internet network, so that problems can be resolved properly. and for monitoring and reporting daily employee attendance can be directly seen and displayed. From the problems above, the writer uses the coloring method to monitor employee attendance and assisted by sequential search for the employee tracking process